The Transmission of SARS-CoV-2 from COVID-19-Diagnosed People to Their Pet Dogs and Cats in a Multi-Year Surveillance Project - Anne K. Kimmerlein; Talon S. McKee; Philip J. Bergman; Irina Sokolchik; Christian M. Leutenegger (Viruses, 2024)
Recent emerging zoonotic disease outbreaks, such as that of SARS-CoV-2, have demonstrated the need for wider companion animal disease surveillance. We tested 1000 dogs and cats belonging to employees of a US veterinary hospital network that were exposed to human COVID-19 cases in the household between 1 January 2020 and 10 March 2022 for SARS-CoV-2 and surveyed their owners about clinical signs and risk factors. The seropositivity was 33% for 747 dogs and 27% for 253 cats. Pet seropositivity correlated with the US human case rates over time, exhibiting peaks corresponding with the major COVID-19 surges. Antibodies persisted longer than previously documented (828 days in dogs; 650 days in cats). Increasing age and duration of proximity to infected people were associated with increased seropositivity in dogs but not cats. Cats were more likely to have clinical signs, but an association between seropositivity and the presence of clinical signs was not found in either species.